1998
DOI: 10.1007/pl00006319
|View full text |Cite
|
Sign up to set email alerts
|

A unique fungal lysine biosynthesis enzyme shares a common ancestor with tricarboxylic acid cycle and leucine biosynthetic enzymes found in diverse organisms

Abstract: Fungi have evolved a unique alpha-amino-adipate pathway for lysine biosynthesis. The fungal-specific enzyme homoaconitate hydratase from this pathway is moderately similar to the aconitase-family proteins from a diverse array of taxonomic groups, which have varying modes of obtaining lysine. We have used the similarity of homoaconitate hydratase to isopropylmalate isomerase (serving in leucine biosynthesis), aconitase (from the tricarboxylic acid cycle), and iron-responsive element binding proteins (cytosolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 27 publications
(31 reference statements)
3
36
0
Order By: Relevance
“…4). The general topology of the tree is very similar to published trees of the aconitase family (53,57,58). TbACO is clearly separated from the mitochondrial aconitases.…”
Section: Sacii-pstisupporting
confidence: 61%
“…4). The general topology of the tree is very similar to published trees of the aconitase family (53,57,58). TbACO is clearly separated from the mitochondrial aconitases.…”
Section: Sacii-pstisupporting
confidence: 61%
“…By comparison, the lysine growth requirement of isa⌬ strains cannot be explained by a similar aconitase deficiency, since yeast aco1 mutants are not lysine auxotrophs. The lysine biosynthetic pathway in yeast utilizes a single Fe-S enzyme, a fungal specific [4Fe-4S] homoaconitase presumed to be mitochondrial in location (18,47,51). Although it was not possible to obtain comparative measurements of homoaconitase activity, a defect in this enzyme is a likely cause of the lysine auxotrophy.…”
Section: Resultsmentioning
confidence: 99%
“…One is the diaminopimelate (DAP) pathway starting from aspartate via DAP, as seen in most bacteria and plants, the other is the Kaminoadipate (AAA) pathway from 2-oxoglutarate via AAA, as seen in yeast [1] and fungi [2,3]. In our recent studies, however, an extremely thermophilic bacterium, Thermus thermophilus HB27, was shown to synthesize lysine not via DAP, but through AAA [4].…”
Section: Introductionmentioning
confidence: 99%